Role of muscle activation in the sit-skiing performance and classification process - Rapp, W.; Rosso, V.; Ohtonen, O.; Gastaldi, L.; Vanlandewijck, Y.; Lindinger, S. J.; Linnamo, V. (Sciene and nordic skiing III, 2016)
In classical skiing the use of DP has increased during the past years in particular after sprint skiing competitions started in the late 1990`s. It seems that in the future the relative use of DP may increase even with long distance races. In world cup 15km classical race in December 2014 in Davos (Switzerland), for the first time three skiers in the top 10 skied the whole race using DP and the race was won with this technique for the first time in Toblach (Italy) in January 2015. Therefore it can be concluded that DP technique may be most economical when skiing on flat or slight uphill while in a steeper uphill this advantage is lost (Pellegrini et al 2013). As known from cross-country skiing studies in able bodied skiers double poling (DP) shows a highly complex biomechanical pattern requiring high pole forces, varied joint kinematics and high complex muscle activity of numerous upper body muscles (Holmberg et al. 2005; Holmberg et al. 2006; StOggl et al. 2007; Lindinger et al. 2009; Lindinger & Holmberg 2011). Moreover, double poling with its numerous degrees of freedom requires a high range of movement variability in training with variations in cycle characteristics (cycle rate and length; ground contact and recovery times, etc.), pole force transfer to the ground, kinematics (elbow/shoulder/trunk joint and pole angles) and muscular activity. In Paralympic Nordic sit skiing, the technique of double poling is the only possibility to generate forward propulsion. Comparison of DP technique between disabled and non-disabled however must reflect differences due to the impairment of the disabled athletes. First of all the individual impairment requires different sitting positions which cause different biomechanical relevant conditions.